Interaction of computer technology and school reform - Ališauskas, Ričardas (Information & Media, 1997)
This article deals with some problems of contemporary school reform due to computer technology. The contemporary directions of educational philosophy, psychology, and social forecasting are considered. The main methods of using computer technology and information management in the schools are discussed: Computer Science teaching, computer assisted learning, and contemporary school management. Logo educational philosophy and hypertexts are introduced.